Learning of Inquiry Sequences-Based E-Student Worksheet Assisted by Canva to Stimulate Hands-On Skills, Mind-On Activity, and Science Process Skills - Divia, Bizry Cahya; Herlina, Kartini; Viyanti, Viyanti; Abdurrahman, Abdurrahman; Ertikanto, Chandra (Universitas Islam Negeri Raden Intan Lampung, 2022)
The covid-19 pandemic has changed educational policies regarding learning and teaching methods that were initially conventional and must now be integrated with technology. It takes teaching materials that can help students in learning. This study aims to develop an E-student worksheet using the Canva-assisted learning of inquiry sequences (LOIS) learning activity model that can be applied as a physics learning material that can practice hands-on skills, mind-on activities, and science process skills. This study uses research and development research methods. The E-student worksheet development procedure uses the ADDIE development model. The results of the experts show that the average score of the assessment of the E-student worksheet is 3.58, which is included in the very valid criteria. The limited trial of the E-student worksheet on the teacher's perception obtained results of 91% in the very good category, the test results for class XI students could be applied with a very good 88% score. The results of the effectiveness of working on the E-student worksheet obtained an average score of 89% in the highly trained category. It can be concluded that which means the E-student worksheet can train hands-on, minds-on activity, and science process skills.